SISTEM INFORMASI PENGELOLAAN BEASISWA PADA KOPERTIS WIAYAH X - Elgi Janliza Putra; Dony Novaliendry; Titi Sriwahyuni (Universitas Negeri Padang, 2014)
This study is based from a case in KOPERTIS Region X about scholarship management process that was done manually and spend a lot of time. From this case, a Scholarship Management Information Systems is designed to assist KOPERTIS Region X in scholarship management.Scholarship Management Information System was developed using Waterfall Mode, which starts with the specification of user needs and continued by planning, modelling, construction, delivering system to the deployment, and finally the system maintenance. Scholarship Management Information System is designed by using the web-based programming language such as HTML, PHP5, CSS, JavaScript, Ajax, jQuery and MySQL databases. From this study, a web-based system of Scholarship Management Information Systems is created at KOPERTIS Region X to help the performance of KOPERTIS Region X in scholarship management. Keyword : Management Information System, Waterfall Mode, PHP, MySQL.